Metabolic Syndrome features and risk of neural tube defects - Wong Pui-Yuen; Wyatt Philip R; Meier Chris; Vermeulen Marian J; Thompson Miles D; Ray Joel G; Summers Anne M; Farrell Sandra A; Cole David EC (BMC, 2007)
Abstract Background Maternal obesity and pre-pregnancy diabetes mellitus, features of the metabolic syndrome (MetSyn), are individual risk factors for neural tube defects (NTD). Whether they, in combination with additional features of MetSyn, alter this risk is not known. We evaluated the risk of NTD in association with maternal features of the MetSyn. Methods We used a population-based case-control study design in the province of Ontario, Canada. Cases and controls were derived from women who underwent antenatal maternal screening (MSS) at 15 to 20 weeks' gestation. There were 89 maternal cases with, and 434 controls without, an NTD-affected singleton pregnancy. Maternal features of MetSyn were defined by the presence of pre-pregnancy diabetes mellitus, body weight ≥ 90th centile among controls, non-white ethnicity and/or serum highly sensitive C-reactive protein (hsCRP) ≥ 75th centile of controls. Since hsCRP naturally increases in pregnancy, analyses were performed with, and without, the inclusion of hsCRP in the model. Results Mean hsCRP concentrations were exceptionally high among study cases and controls (6.1 and 6.4 mg/L, respectively). When hsCRP was excluded from the model, the adjusted odds ratios for NTD were 1.9 (95% confidence interval 1.1-3.4) in the presence 1 feature of MetSyn, and 6.1 (1.1-32.9) in the presence of 2 or more features. When hsCRP was included, the respective risk estimates were attenuated to 1.6 (0.88-2.8) and 3.1 (1.2-8.3). Conclusion We found about 2-fold and 6-fold higher risk for NTD in the presence 1, and 2 or more features, of the metabolic syndrome, respectively. It is not clear whether this risk is altered by the presence of a high serum hsCRP concentration.